Alternative Strategies for the Treatment of Classical Congenital Adrenal Hyperplasia: Pitfalls and Promises. (8th June 2010) - Loechner, Karen J.; McLaughlin, James T.; Calikoglu, Ali S.
Abstract : Despite decades of different treatment algorithms, the management of congenital adrenal hyperplasia (CAH) remains clinically challenging. This is due to the inherent difficulty of suppressing adrenal androgen production using near physiological dosing of glucocorticoids (GC). As a result, alternating cycles of androgen versus GC excess can occur and may lead to short stature, obesity, virilization, and alterations in puberty. Novel therapeutic alternatives, including new and more physiological means of GC delivery, inhibitors at the level of CRH or ACTH secretion and/or action, as well as "rescue strategies", such as GnRH analogs, anti-androgens, aromatase inhibitors, and estrogen receptor blockers, are available; many of these agents, however, still require active investigation in CAH. Bilateral adrenalectomy is effective but it is also still an experimental approach. Gene therapy and stem cells, to provide functional adrenal cortical tissue, are at preclinical stage but provide exciting avenues for a potential cure for CAH.